Effects of contextual interference (CI) in basic squash shots practice / Ebby Waqqash and Jeffrey Low - Waqqash, Ebby; Low, Jeffrey (Faculty of Sports Science and Recreation, 2015)
The purpose of this study was to compare block and random practice in learning basic squash shots. Eight university students were randomly assigned to two groups; the block practice group and the random practice group. The block practice group performed 10 minutes of forehand stroke, followed by another 10 minutes of backhand stroke. The random practice group played against themselves in a 1 on 1 real-match situation for 20 minutes. Three tests were administered to evaluate the participants’ performance: pretest, posttest (acquisition) and retention test. Results showed the block practice (M=16, SD=.816) has better skill learning effect in the acquisition phase compared to random practice (M=15.75, SD=2.22). However, the random practice (M=18.25, SD=2.22) outperformed the block practice (M=10.25, SD=1.26) in the retention phase. Based on the finding of this study, unstructured and real-match situation practice facilitates better learning by reconstructing the learners’ action plan each time a skill is performed.